2018
DOI: 10.1590/1809-6891v19e-25316
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros E Tendências Genéticas Para Características Produtivas De Bovinos Da Raça Nelore

Abstract: Resumo A região Centro-Oeste tem se destacado como produtora de carne bovina e, para tanto, produzir com eficiência tem sido a meta dos produtores. Nesse sentido, objetivou-se estimar parâmetros e tendências genéticas para pesos aos 240 (P240) e 420 (P420) dias de idade em bovinos da raça Nelore, criados na região de Goiás, Brasil. Utilizaram-se 48.580 dados para P240 e 28.685 para P420. Os parâmetros genéticos foram obtidos por análises univariadas em que o modelo continha os efeitos fixos de grupo de contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Maternal heritability estimates in single-and multi-trait analysis were low and similar to those reported by Baldi et al (2010): 0.06 for birth weight, 0.09 for weaning weight, and 0.05 for weight at 12 months. Souza et al (2018) found values close to those observed in this study for weaning weight (h 2 m = 0.06). These values suggest a smaller selection focus for this trait in the northern region of Brazil since the obtained heritability value was of low magnitude.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Maternal heritability estimates in single-and multi-trait analysis were low and similar to those reported by Baldi et al (2010): 0.06 for birth weight, 0.09 for weaning weight, and 0.05 for weight at 12 months. Souza et al (2018) found values close to those observed in this study for weaning weight (h 2 m = 0.06). These values suggest a smaller selection focus for this trait in the northern region of Brazil since the obtained heritability value was of low magnitude.…”
Section: Resultssupporting
confidence: 91%
“…For the beef, cattle production system to be efficient and profitable, the knowledge of the population, geneticphenotypic parameters, and trends in the productive and reproductive characteristics of the herd is extremely crucial, mainly because of the low number of herds evaluated in the northern region of the state. Brazil, which makes selecting genetically superior animals for breeding difficult (Lopes et al, 2017;Souza et al, 2018). Thus, to make an accurate selection, knowing the genetic potential of these animals becomes paramount.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations